2020
DOI: 10.1177/2277975220953311
|View full text |Cite
|
Sign up to set email alerts
|

Social and Financial Efficiency: A Study of Indian Microfinance Institutions

Abstract: Microfinance institutions (MFIs) provides savings, credit, insurance and remittance facilities to more impoverished people without any collateral. MFIs have twin goals: social outreach and financial sustainability. Outreach refers to how many people are served by MFIs while the capacity of MFIs to serve longer is financial sustainability. The social and financial performance of MFIs is the most debatable issue in the Indian microfinance industry. Social efficiency indicates MFIs’ willingness to support a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…The Indian microfinance sector has made significant progress in reaching out to the financially excluded, and studies have shown that microfinance does have a beneficial impact on the poor's well-being (Amarnani & Amarnani, 2015). However, the lack of access of a considerable chunk of the Indian population to the traditional banking system still leaves a lot of prospects for the MFIs to expand their financial services (Chauhan, 2021). In India, there are two prominent microfinance models, namely, the 'self-help group (SHG)-Bank linkage programme (SBLP)' and the 'MFI' model.…”
Section: Summary Of the Indian Microfinance Industrymentioning
confidence: 99%
“…The Indian microfinance sector has made significant progress in reaching out to the financially excluded, and studies have shown that microfinance does have a beneficial impact on the poor's well-being (Amarnani & Amarnani, 2015). However, the lack of access of a considerable chunk of the Indian population to the traditional banking system still leaves a lot of prospects for the MFIs to expand their financial services (Chauhan, 2021). In India, there are two prominent microfinance models, namely, the 'self-help group (SHG)-Bank linkage programme (SBLP)' and the 'MFI' model.…”
Section: Summary Of the Indian Microfinance Industrymentioning
confidence: 99%
“…As per Balkenhol (2007), one-time financial assistance would not help to reduce the poverty of any nation; however, continuity of getting financial aid will help. Efficiency is a crucial instrument to check the performance and sustainability of these institutions (Chauhan, 2021a;Widiarto et al, 2015) Initially, MFIs in India have been operating in various forms like trust, societies, Sec. 25 companies, called NGO-MFIs (non-government organisations-microfinance institutions).…”
Section: Introductionmentioning
confidence: 99%
“…As NBFC-MFIs have a large client base, the performance of these MFIs is crucial for the betterment of the unprivileged society in the long run. To serve the more significant number of the financially excluded population, these institutions must be financially and socially efficient, as these institutions have double bottom line objectives (Chauhan, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations